Sustainable Tourism Development through Local Wisdom in Pentingsari, Yogyakarta - Husen, Emir Faisal; Sari, Tasya Komara; Hutagalung, Husen (Indonesian Tourism Journal, 2025)
This study explores the pivotal role of local wisdom in fostering sustainable tourism development in Pentingsari Tourism Village, Yogyakarta, against the backdrop of mass tourism’s threats to environmental integrity and sociocultural continuity. The research aims to identify key elements of local wisdom, examine their interaction with tourism practices, and assess their contribution to sustainability frameworks. Adopting a qualitative approach, data were collected through in-depth interviews, participant observation, focus group discussions, and document analysis, then analyzed using Miles and Huberman’s interactive model supported by Interpretative Phenomenological Analysis to uncover emergent themes. Findings reveal that values such as gotong royong (mutual cooperation), environmental stewardship, Islamic ethical norms, and cultural preservation are deeply embedded in tourism governance and provide resilience against crises, including the 2010 Merapi eruption and COVID-19 pandemic. Community participation, particularly through youth organizations, strengthens cultural transmission and innovation, while partnerships with government, NGOs, and the private sector enhance institutional capacity and economic empowerment. Pentingsari demonstrates that prioritizing quality over quantity of visitors, developing nature-based educational tourism, and integrating traditional knowledge into modern tourism practices generate inclusive economic benefits, cultural pride, and ecological responsibility. The conclusion underscores that Pentingsari offers a replicable model of community-based tourism rooted in local wisdom, balancing cultural vitality, environmental care, and economic viability. However, the study also highlights challenges of cultural commodification, dependency on tourism markets, and ecological carrying capacity, suggesting the need for further research on scalability across diverse socio-cultural contexts.